A review of europe’s circular economy in the building sector - Mrad, Cyrine (2022)
This article evaluates Europe’s building sector’s circular economy (CE). This industry is responsible for 42% of energy consumption, more than 50% of extracted materials, 30% of Europe’s water and waste generation, and 35% of greenhouse gas (GHG) emissions. This study focuses on peer-reviewed articles from Scopus and Web of Science databases. Of the first 1750 publications, 2.9% were eligible for a full-text reading and analysis. Most of the trending studies, 92%, promote the circular economy concept through construction materials rather than analyzing the impact of the construction sector on the environment and finding solutions for better implementation, and 41% promote recycling and reuse as the only options. New Design solutions are in 12% of the studies, six-fold more than Law and Legislation, which is only 2%. Finding an optimal combination of assessing the life cycle of buildings and components and searching for different ways of managing the Construction and Demolition Waste at end-of-life is between 33% and 39%. Ultimately, CE proposed frameworks for the building industry based on 10R principles variations were evaluated. An alternative framework for a circular strategy for the building industry that focuses on Upcycling, replacing the Recover principle is presented.